2021
DOI: 10.1093/jxb/erab434
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and thermal sensitivity of rRNA maturation paths in plants

Abstract: Ribosome biogenesis is a constitutive fundamental process for cellular function. Its rate of production depends on the rate of maturation of precursor ribosomal RNA (pre-rRNA). The rRNA maturation paths are marked by four dominant rate-limiting intermediates with cell-type variation of the processivity rate. We have identified that high temperature stress in plants, while halting the existing pre-rRNA maturation schemes, also transiently triggers an atypical pathway for 35S pre-rRNA processing. This pathway le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 81 publications
4
24
0
Order By: Relevance
“…In agreement with our results, it was recently reported that 1 h exposure at high temperatures (from 30 to 42°C) provoke significant changes in the accumulation of pre-rRNAs 35SA 123 B/35S*, 35S, 32S, 27S, P-A3, 18-A3 and P-P1 in rosette leafs from Arabidopsis plants [ 53 ]. Indeed, in Arabidopsis seedlings a rapid reduction of 27SA, P-A3, 18-A3 and P-P1 was also detected after 2 h at 37°C while 35S pre-rRNA levels increased to decrease gradually after 3 h at 37°C ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, it was recently reported that 1 h exposure at high temperatures (from 30 to 42°C) provoke significant changes in the accumulation of pre-rRNAs 35SA 123 B/35S*, 35S, 32S, 27S, P-A3, 18-A3 and P-P1 in rosette leafs from Arabidopsis plants [ 53 ]. Indeed, in Arabidopsis seedlings a rapid reduction of 27SA, P-A3, 18-A3 and P-P1 was also detected after 2 h at 37°C while 35S pre-rRNA levels increased to decrease gradually after 3 h at 37°C ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, heat stress reduces (35%–36%) the processing of such 35S pre-rRNAs into P-A3, and concomitantly correlates with an 2–3 fold increase in the rate of P-A3 processing/degradation. Notably, we have found a transformation rate (k s−1 ) of 35 into P-13 (α*k 35S ) of (3.6–25)x10 −5 , which is similar in order of magnitude to the k 4 (2.4 ± 0.4) x10 −5 estimated by pulse-labelling experiments with heat stress at 38°C [ 53 ]. Accordingly, these estimations suggest that significant changes in the processing rates of specific rRNAs are required to impair ITS1-first (and likely 5’ETS-first) once plants are exposed to heat stress conditions.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…5B; probe P5, marked with an arrowhead). This species most likely corresponds to a stress-related P-C2 intermediate that was initially identified in irp7 mutants upon auxin treatment and represents a bypass pre-rRNA processing pathway called ‘ITS2-first’, in which the initial cleavage of the primary precursor occurs at site C2 within ITS2 (Palm et al ., 2019; Sáez-Vásquez and Delseny, 2019; Shanmugam et al ., 2021; Darriere et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, several Arabidopsis pre-rRNA processing mutants exhibit altered sensitivity to various stressors (e.g. irp (Palm et al ., 2019), apum23 (Huang et al ., 2018), apum24 (Maekawa et al ., 2018)) and the plant response to abiotic stresses includes altered expression of pre-rRNA processing factors and changes in the pre-rRNA maturation pathway (Palm et al ., 2019; Sáez-Vásquez and Delseny, 2019; Martinez-Seidel et al ., 2020; Shanmugam et al ., 2021; Darriere et al ., 2022). In response to stress, the expression of RP genes is regulated, inter alia, by the TOR signaling pathway (Petibon et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%